Carbon Emissions, Corporate Social Responsibility, and Environmental Costs: Evidence on Energy Firms - Firda Avcarina; Adri Putra Nugraha (Majapahit Journal of Islamic Finance and Management, 2026)
The increase in greenhouse gas emissions and the discrepancy between reported emissions and actual conditions have made the energy sector a major focus of attention for regulators and investors regarding sustainability issues. This study aims to analyze the effect of carbon emission disclosure, corporate social responsibility (CSR), and environmental costs on firm value, using company size, profitability, and age as control variables. The study used a causal quantitative design with secondary data from 27 energy sector companies listed on the Indonesia Stock Exchange for the 2020–2024 period, analyzed using multiple linear regression. The results show that carbon emission disclosure has a significant negative effect on firm value, while CSR and environmental costs have a significant positive effect. These findings imply that companies need not only to improve environmental transparency but also to develop effective risk mitigation and sustainability management strategies so that non-financial information can be interpreted as a positive signal by investors and support long-term value creation.